PATRIARCHAL REPRESENTATION OF FATHIYA IN YUSUF IDRIS’S SHORT STORY “AN-NADAHAH”: A RADICAL FEMINIST LITERARY ANALYSIS: Analisis Feminisme Radikal - Rimawan, Aisya; Ekawati, (Hijai - Journal on Arabic Language and Literature, 2026)
This study examines the representation of patriarchy and female resistance through the character of Fathiya in Yusuf Idris’s short story An-Nadahah (1962). Employing Kate Millett’s radical feminist theory, the research analyzes how patriarchal domination operates through sexual violence, male passivity, and the internalization of oppressive values within female consciousness. Using a qualitative approach with close reading techniques, the findings reveal that patriarchy functions not only as an external system of male domination, embodied by Afandi’s sexual violence, but also through Hamed’s silence and failure as a husband. Furthermore, the study demonstrates that Fathiya internalizes patriarchal norms that frame silence, shame, and self-sacrifice as moral imperatives. This analysis highlights how patriarchy controls women both structurally and psychologically, reinforcing the relevance of radical feminist theory in literary criticism. Keywords: Patriarchy, Radical Feminism, and Yusuf Idris’s Short Story “An-Nadahah”